Imperialism and the political economy of global south's debt - Sylla, Ndongo Samba (Emerald Publishing Limited, 2023)
The Covid-19 pandemic has brought the nagging issue of the Global South's debt back into the spotlight. With declining export earnings and tax revenues, many countries in Africa, Latin America and Asia have found themselves objectively unable to service their foreign currency debt. This situation, reminiscent of the international debt crisis of the 1980s and 1990s, is the backdrop of the 38th volume of the Research in Political Economy series edited by Ndongo Samba Sylla. In Imperialism and the Political Economy of Global South's Debt, expert contributions connect the history of this issue with a range of factors including class dynamics, the changing landscape of sovereign debt markets, the global liquidity cycle, the enduring constraints of commodity dependence, ecological sustainability and the limitations of the current ad hoc sovereign debt restructuring procedures. In contrast to orthodox accounts that view debt crises in the Global South as a cyclical problem or as consequences of 'mismanagement' or 'fiscal irresponsibility'. Imperialism and the Political Economy of Global South's Debt recognises the systemic nature of the Global South's external debt, revealed only further by the economic uncertainty of the Covid-19 pandemic, as well as the need to analyse it in relation to existing imperialist structures.
Keywords: Imperialism -- Economic aspects.; Developing countries -- Economic conditions.; Debt -- Developing countries.; Business & Economics -- Development -- Economic Development.; Development economics & emerging economies.; elektronické knihy; electronic books